Marketing to Children : A Reflection of Institutional Psychopathy - Raja Reddy, T.; Lokanadha Reddy, E.; Narayana Reddy, T. (Indian Journal of Marketing, 2016)
Children buy products, pester their parents to buy, and are potential future buyers. Such potential profitability has attracted the attention of marketers, who aggressively target children in their quest for markets and products. Marketers disregard the human aspects in the process of exploiting the vulnerabilities of children, leading us to the argument that 'marketing to children' is a reflection of 'institutional psychopathy'. Psychopathy or antisocial personality disorder involves major abnormality characterized by lack of empathy, inappropriate behaviour, and indifference to rights and feelings of others. When businesses, the powerful institutions of our society, exhibit these characteristics, they are termed 'institutional psychopaths'. In this paper, the diagnostic checklist for antisocial personality disorder issued by the American Psychiatric Association in Diagnostic and Statistical Manual of Mental Disorders was applied to argue that marketers targeting children are in fact psychopaths, exhibiting psychological abnormalities. On application of the checklist, it was found that marketers targeting children scored a perfect seven on the diagnostic checklist, a definite reflection of 'institutional psychopathy'.